ICTs application and its relationship to job performances of extension workers in North Central Nigeria - Bakari, Dalibu; Man, Norsida; Mohd Nawi, Nolila; Arif Shah, Jasmin (Journal of Global Innovations in Agricultural and Social Sciences (JGIASS), 2023)
The study centered on (ICTs) application and its relationship to the job performances of extension workers in North central Nigeria. A structured questionnaire was administered to 291 extension workers. A sampling method with a mixture of techniques was adopted. Descriptive statistics, Z test, Pearson correlation, and Factor analysis were employed. A significant majority 87.6 % often used Facebook, 86.9% What’s app, and 84.2% internet sources/mobile/smartphone. Factors affecting ICTs application, Factor 1 having high loading were lack of availability of professionals for training, gender issues, lack of Government intervention, and lack of monitoring and evaluation from the government. Factor 2 with higher loading was the need for ICTs infrastructure and inadequate availability of electricity. Factor 3 with high loading was high equipment cost and poor income. Among the three factors that contributed most to explaining the total challenges of ICTs training and application is factor 1 with about 20.5%, followed by factor 2 which accounted for 18.6%. There was a significant difference between gender and performances at a 0.05 level. There was a positive and moderate effect and significant correlation at 0.01 level between ICTs application (r=0.309) and job performance at P<0.01. ICTs application also had a small effect and Positive and significant association with the Quantity of work, quality of work, and speed of work at a 1% level of significance. It is recommended that the Government should intervene through equality professional training and set up a good monitoring team to encourage effective ICTs applications directed towards organizational development. Keywords: ICTs, application, relationship, performances, extension workers.